The Effect of Hydroton Planting Media with Various Organic Material Compositions on the Growth and Productivity of Pakcoy Plants (Brassica Rapa L) - Tiara Putri Dwi Dayani; Edy Suryadi; Sophia Dwiratna (Jurnal Pertanian Tropik, 2019)
The hydroton planting media that is marketed has the characteristics of low water holding capacity. The addition of organic material in the form of husk charcoal, cocopeat, and compost clay can increase the water holding capacity of the hydroton so that plant productivity increases. This study aims to determine the composition of the best planting media for pakcoy plant growth in hydroponic floating raft systems. The research was carried out at the Rooftop of the Food Building of the Faculty of Agricultural Industrial Technology, Padjadjaran University. The experiment was arranged using a completely randomized design that was repeated four times and seven combinations of treatments. The composition of organic matter is added as much as 2.5% and 5% of each organic material. The variables observed were plant height, the number of leaves, root length, leaf area, wet weight, and stover weight. All data were analyzed using ANOVA followed by DMRT test at the level of 5%. The results showed that the organic matter in hydroton had a role in the parameters of growth and productivity of pakcoy plants compared to hydroton materials without comparing organic matter and the weight of root wet. The treatment of adding organic matter in the form of (husk charcoal, 5%) and (Cocopeat, 5%) is a treatment that affects the root length and weight of root wet.